Lipidomic profiling reveals systemic serum lipid remodeling induced by dexamethasone in mice - Zhang, Aiping; Wang, Zhao; Ji, Jianjian (Frontiers in Molecular Biosciences, 2025)
BackgroundDexamethasone is a commonly used glucocorticoid medication in pediatrics. However, dexamethasone is associated with some side effects, such as dyslipidemia. This study aimed to explore the effects of dexamethasone on the serum lipidome.MethodsWe utilized Exactive Orbitrap-MS technology to assess the effects of dexamethasone intervention on serum lipids in mice. ResultsUnbiased Principal Component Analysis (PCA) revealed that dexamethasone intervention significantly induced changes in serum lipids in mice, and after a 7-day washout period (equivalent to 28 drug half-lives), changes of lipids in the serum were still existed compared with those in the control groups. After 4 days of dexamethasone injection, significant changes were observed, including 16 increased lipids, and 1 decreased lipid in the serum compared with those in the control groups. After a 7-day washout period, some of lipids in the serum were still changed, including 5 increased lipids, such as Acylcarnitines (CAR), ceramides (Cer), diacylglycerophosphates (DG), lysophosphatidylglycerol (LPG) and phosphatidylglycerol (PG), 1 decreased lipid, hexosylceramides (HexCer), indicating dexamethasone may result in long-term changes of lipids in the serum. DiscussionIn conclusion, utilizing a lipidomics method, we provide the first complete proof that dexamethasone intervention generates extensive modification of the serum lipidome.